Gender dynamics in a masculine professional context: The case of the Portuguese Air Force - Santos, M. H. (2022)
This article aims to understand the experiences of women working in the Portuguese Air Force, a traditionally male professional environment, and the perspectives of their male counterparts on the subject, considering women’s minority status and symbolic gender asymmetries in the military. This study draws on 16 semi-structured interviews with Air Force personnel, evenly split by gender. Findings reveal four main themes that convey awareness that the Air Force is still a masculine world, perceptions of gender dynamics in the Air Force, barriers to equality, and strategies to address the situation. Although gender equality is formally in place in the Air Force, women continue to face obstacles that hinder their career advancement and ensure that their professional experiences differ from those of their male counterparts.